Pendampingan Pengelolaan Toilet Bersih Berbasis Standar Asean Di Destinasi Wisata Kabupaten Klungkung - I Gusti Bagus Agga Wiguna; I Wayan Eka Sudarmawan (Pusat Riset dan Inovasi Nasional, 2025)
The quality of public toilets at tourist destinations is a crucial indicator in providing a clean, safe, and sustainable travel experience. Based on the ASEAN Public Toilet Standard (APTS), toilet management must fulfill criteria related to cleanliness, safety, accessibility, and environmental sustainability. This community service program aimed to enhance the capacity of sanitation staff at tourist destinations in Klungkung Regency, through training and mentoring activities aligned with APTS. The methods used included a participatory approach, training and demonstrations, as well as Focus Group Discussions (FGDs). The results showed improved understanding among participants regarding hygiene practices, appropriate chemical selection, and the implementation of safety protocols in public toilet facilities. The program also strengthened collaboration between field staff and the Department of Tourism in forming a shared commitment to uphold standardized public services. The implementation of APTS is expected not only to improve public toilet quality but also to support sustainable tourism goals across the ASEAN.